Free speech handbook : a practical framework for understanding our free speech protections - Rosenberg, Ian (World citizen comics., 2025)
"Freedom of speech is perhaps the most American of virtues. In a nation where everyone wants to speak and be heard, the First Amendment right is vital to our identity and our democracy. The civil liberties it confers have been advanced by people who spoke out and fought in our nation's highest court, with each decision refining and reshaping what exactly "free speech" means. In Free Speech Handbook, Ian Rosenberg and Mike Cavallaro brilliantly trace this turbulent history across ten seminal Supreme Court cases while drawing parallels with more recent controversies. Rosenberg's straightforward language combines with Cavallaro's bold and bright art to create an accessible and engaging crash course on the meaning, reach, and limits of our free speech protections."--Book flap